"Palace of the Peacock". Wilson Harris and the scansion of language - Pavez, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
Wilson Harris’s first novel, The Palace of the Peacock (1960), narrates the journey of a river expedition through the jungles of Guyana. This novel has been read as being determined by the search for identity or a kind of destined truth, represented by the almost symbolic-mystical journey of characters in whose development they understand themselves. In contrast to an identitarian reading, the essay proposes that Harris has no ownership of language and no language of his own. Thus, Issues of passage, threshold, and crossing run through the narrative. Grammar, semantics, and syntax are twisted. Like the temporality of the story, the syntactic relations enter into a sort of ellipsis or spiral. Thus, rather than expression of a previous content, fulfillment or reconstitution, language is limbo. If there is no originary language, The Palace of the Peacock thus names the scansion of language